Risk of hypothyroidism in meat-eaters, fish-eaters, and vegetarians: a population-based prospective study - Candussi, Catharina J; Bell, William; Thompson, Alysha S; Knüppel, Sven; Gaggl, Martina; Světnička, Martin; Gojda, Jan; Cassidy, Aedín; Weikert, Cornelia; Córdova, Reynalda; Kühn, Tilman (BMC medicine, 2025)
BACKGROUND: Plant-based diets are gaining popularity due to their well-documented cardiometabolic benefits and environmental sustainability. However, these diets are often lower in specific micronutrients such as iodine, raising concerns about their potential impact on thyroid health. Therefore, we examined the associations between plant-based diets and the risk of hypothyroidism. METHODS: We analysed data from the UK (United Kingdom) Biobank cohort. Multivariable Cox proportional hazards regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (95% CIs) for incident hypothyroidism across vegans, vegetarians, pescatarians, poultry-eaters, low meat-eaters, and high meat-eaters aged 40-69 years. Ancillary to this, we carried out logistic regression analyses to evaluate associations between the diet groups and prevalent hypothyroidism according to International Classification of Diseases (ICD) codes at baseline. RESULTS: We included 466,362 individuals from the UK Biobank, of which 220,514 followed a high meat, 221,554 a low meat, 5242 a poultry-based, 10,598 a pescatarian, 8057 a vegetarian, and 397 a vegan diet. During a median SD (Standard Deviation) follow-up of 12.7 (± 3.2) years, 10,831 participants developed hypothyroidism. In multivariable Cox regression models without adjustment for body mass index (BMI), none of the diets were significantly associated with the risk of hypothyroidism. However, there was a tendency for a higher risk of hypothyroidism among vegetarians compared to people following a high meat diet (HR = 1.13, 95% CI 0.98-1.30). After controlling for BMI, a potential collider, the association for vegetarians (HR = 1.23, 95% CI 1.07-1.42) became stronger and statistically significant. Furthermore, we observed a positive association between low meat-eaters (OR = 1.05, 95% CI 1.03-1.08), poultry-eaters (OR = 1.15, 95% CI 1.04-1.28), pescatarians (OR = 1.10, 95% CI 1.01-1.19) and vegetarian (OR = 1.26, 95% CI 1.15-1.38) with hypothyroidism prevalence. CONCLUSIONS: In the present study, we found a moderately higher risk of hypothyroidism among vegetarians, after controlling for BMI, a potential collider. This slightly higher risk of hypothyroidism among vegetarians requires further investigation, taking iodine status and thyroid hormone levels into account.
Keywords: dieta; Thyroid; dospělí; Risk Factors; Spojené království; ženské pohlaví; Proportional Hazards Models; Hypothyroidism; lidé; prospektivní studie; dieta vegetariánská; Plant-based diets; Vegan; Vegetarians; Meat; senioři; Aged; lidé středního věku; hypotyreóza; Animals; Vegetarian; vegetariáni; Humans; Diet; proporcionální rizikové modely; Prospective Studies; Iodine; zvířata; Diet, Vegetarian; mužské pohlaví; Adult; Male; rizikové faktory; maso; United Kingdom; Middle Aged; Female